Pengaruh Sosial Media dalam Rumah Tangga di Desa Sialang Kecamatan Bangun Purba Kabupaten Deli Serdang - Evalinda Sinaga, Ester (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
The emergence of social media has led to changes in people's behavior patterns according to existing culture, ethics and customs. With a large population and cultural diversity in terms of ethnicity, race and religion, Indonesia has the potential for significant social change. Indonesian people from various backgrounds and ages have and use social media to collect information and convey it to the public. Deli Serdang Regency is one of the administrative regions in North Sumatra. In Deli Serdang district there are several villages, one of which is Sialang Village. Deli Serdang Regency, especially Sialang Village, has 3,362 people, including 969 families. Changing times have made the development of social media increasingly rapid, especially in Sialang Village. Social media also plays a role in the households of the people of Sialang Village and has a more dominant negative impact on households. Qualitative methods were used in this research to determine the influence of social media in the households of the people of Sialang Village, Bangun Purba District, Deli Serdang Regency. The purpose of this research was carried out because many household actors are quite active in using social media, thereby influencing developments in the household. The results of this research are that social media tends to have a negative impact, causing arguments, infidelity, domestic violence and divorce. The efforts made by the people of Sialang Village, Bangun Purba District, Deli Serdang Regency are by maintaining communication within the household, being open to each other, and limiting each other's use of social media in the household.